Phycoeritryn Pigments In Carrageenan From Algae Kappaphycus alvarezii (Doty) Doty 1996 - Tumalun, Abigael Joanete; Mantiri, Desy Maria Helena; Paransa, Darus Sa'adah Johanis; Rompas, Rizald Max; Kemer, Kurniati; Mudeng, Joppy (Jurnal Ilmiah Platax, 2022)
Kappaphycus alvarezii is a marine alga cultivated in Indonesia and produces carrageenan. Carrageenan is a product used in the cosmetic, food, and pharmaceutical industries. This study aimed to test the viscosity and gel strength of refined carrageenan with the addition of natural dye phycoerythrin from the algae Halymenia durvillei with different concentrations. Refine carrageenan was made using alkaline solvents of 4% NaOH and 5% KOH and then boiled using a pressure cooker. The results showed a reddish color change in the pure carrageenan refinement with the addition of phycoerythrin pigment, especially at a concentration of 50%. The average value of refined carrageenan viscosity for 4% NaOH concentration was 49.22 – 50.27 cP, and 5% KOH concentration ranged from 47.16 – 50.12 cP. Testing the gel strength of the refined carrageenan, the average NaOH 4% was 72.67 – 82.00 mm/g/sec, and the 5% KOH concentration was 81.00 – 81.78 mm/g/sec. The addition of phycoerythrin pigment to refine carrageenan had no effect on viscosity and gel strength. Drying at a temperature of 100oC obtained a water content of semi-refined carrageenan between 2.91 - 4.38%, this value is in accordance with the standard for carrageenan water content from FAO, which is a maximum of 12%.Keywords: Carrageenan, phycoerythrin pigments, Kappaphycus alvarezii, Halymenia durvillei, viscosity, gel strength.AbstrakKappaphycus alvarezii merupakan alga laut yang dibudidayakan di Indonesia dan penghasil karagenan. Karagenan merupakan suatu produk yang digunakan dalam industri kosmetik, makanan, dan juga farmasi. Tujuan dari penelitian adalah menguji viskositas dan kekuatan gel terhadap karagenan refine yang ditambahkan pigmen fikoeritrin dari alga Halymenia durvillei dengan perbedaan konsentrasi. Karagenan refine dibuat dengan menggunakan pelarut alkali NaOH 4% dan KOH 5% selanjutnya direbus dengan tekanan tinggi. Hasil yang didapat menunjukan bahwa terjadi perubahan warna kemerahan pada karagenan refine dengan penambahan pigmen fikoeritrin, terutama pada konsentrasi 50%. Nilai rata-rata viskositas karagenan refine untuk konsentrasi NaOH 4% adalah 49.22 – 50.27 cP, dan konsentrasi KOH 5% berkisar 47.16 – 50.12 cP. Pengujian kekuatan gel pada karagenan refine diperoleh rata-rata NaOH 4% sebesar 72.67 – 82.00 mm/g/det dan konsentrasi KOH 5% adalah 81.00 – 81.78 mm/g/det. Penambahan pigmen pada karagenan refine tidak berpengaruh pada viskositas dan kekuatan gel. Pengeringan dengan suhu 100OC memperoleh kadar air pada karagenan semi refine antara 2.91 - 4.38%, nilai tersebut telah sesuai dengan standar kadar air karagenan dari FAO yaitu maksimum 12%.Kata kunci: Karagenan, pigmen fikoeritrin, Kappaphycus alvarezii, Halymenia durvillei, viskositas, kekuatan gel.